The association between EPCR gene p.Ser219Gly polymorphism and venous thromboembolism risk: a case–control study, meta-analysis, and a reproducibility study - Pituk, Dóra; Miklós, Tünde; Schlammadinger, Ágota; Rázsó, Katalin; Bereczky, Zsuzsanna (Frontiers in Cardiovascular Medicine, 2023)
The rs867186 single nucleotide polymorphism in the PROCR gene (g.6936A>G, c.4600A>G) results in serine-to-glycine substitution at codon 219 of endothelial protein C receptor (EPCR). We performed a case-control study followed by an updated meta-analysis of the association between this polymorphism and risk of venous thromboembolism (VTE). Objective and methods: We enrolled 263 VTE patients and 320 unrelated healthy controls for the case-control study. The total number of cases and controls for the meta-analysis were 5768 and 30017, respectively. A new online MetaGenyo Statistical Analysis System software was used to perform the current meta-analysis. Furthermore, a reproducibility study was conducted to validate our results. Results: Among well-defined thrombosis risk factors FV Leiden was more frequent in the VTE group (p<0.001), while there was no difference in mutation frequency of prothrombin 20210G>A polymorphism between the groups. There was no difference in mutation frequency of FV Leiden and prothrombin 20210G>A between cases with and without provoking factors and cases with and without VTE recurrence. The rs867186 "G" carriership did not influence the risk of VTE (OR 1.339; 95%CI 0.904-1.984) in our study. No significant differences could be demonstrated among the rs867186 genotype frequencies between VTE cases with and without provoking factors (p=0.430). PROCR rs867186 was associated with an OR 1.72 (95%CI 0.95-3.13), p=0.075 in terms of VTE recurrence. In the meta-analysis a significant association was found between EPCR Ser219Gly polymorphism and VTE under dominant model (OR = 1.27, 95% CI:1.11-1.46, p= 0.0006) recessive model (OR= 1.60, 95% CI:1.26-2.04, p= 0.0001) GG versus AA contrast model (OR = 1.64, 95% CI:1.28-2.09, p= 0.0001) GA versus AA contrast model (OR = 1.24, 95% CI:1.08-1.43, p= 0.002).The rs867186 was not associated with first VTE risk in our case-control study, however a tendency to VTE recurrence was observed. Based on the results of our reproducibility study, MetaGenyo is acceptable for meta-analysis in case of genetic epidemiology studies. Although the risk EPCR p.Ser219Gly and venous thromboembolism 2 conferred by the rs867186 is mild in all meta-analyses, including ours, identifying patients carrying the minor allele might have an impact on personalized VTE risk assessment, risk-score calculation and patient management.